Business Plan dan Pengembangan Model Pembiayaan Akad Murabahah Usaha Konveksi Hijab Syar’i Essentials : Business Plan and Development of Murabahah Agreement Financing Model for Syar'i Essentials Hijab Convection Business - Achmad Riady; Adnan Hasan; Abd. Hafid; Azwar, Azwar; Hamzah Khaeriyah; Abdi Wijaya (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to develop a comprehensive and applicable business plan for the growth of the Syar’i Essentials hijab manufacturing enterprise, as well as to design a financing model based on the murābaḥah contract that is relevant and suitable for micro-enterprises in the Muslim fashion industry. This applied qualitative research uses a case study approach focused on Syar’i Essentials, a startup operating in the modest fashion sector. The findings reveal that a business plan addressing production, marketing, management, and sharia-based financial systems is crucial to ensure the sustainability and integrity of the business. The murābaḥah-based financing model is designed to fulfill capital needs in a halal manner, using a transparent transaction scheme free from riba, gharar, and maysir. The implementation of this model offers a strategic, applicable financing solution that can be replicated in similar micro-scale businesses. This study is expected to provide practical contributions to the strengthening of the sharia-based entrepreneurial ecosystem and the development of Islamic microfinance models.